EVALUATION OF ANTIPROLIFERATIVE ACTIVITY OF SIDDHA ANTI-PSORIATIC FORMULATION PANCHAMUGA CHENDHURAM USING CULTURED HUMAN KERATINOCYTE CELL LINES - RAJALAKSHMI S; RAMYA VT; SAMRAJ K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study was aimed at scientifically evaluating the in vitro antipsoriatic activity of Siddha drug Panchamuga Chendhuram (PMC) in human keratinocyte (HacaT) cell lines. Methods: The Siddha drug PMC tested for antipsoriatic activity on HacaT cell lines was morphologically examined by phase contrast microscopy, and the cell viability was determined by 3- (4, 5 dimethyl thiazole-2 yl) -2.5-diphenyl tetrazolium bromide assay. About 100 μl of different concentrations (2, 6, 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 μg/ml) of the test samples were prepared in the cell culture medium and incubated for 24 h and 48 h to determine the viable cells. Results: The results revealed that Siddha drug PMC showed hopeful antiproliferative activity. In vitro studies showed that after 24 h and 48 h incubation, the inhibitory concentration 50 (IC50) values of PMC (IC50 20 μg/ml) were 72.08±27.56 μg/ml and 43.91±17.71 μg/ml, respectively, as compared with Asiaticoside as a positive control with an IC50 value of 20.13 μg/ml. Conclusion: Thus, this study provides scientific evidence about the efficacy of the Siddha drug PMC against the HacaT cell lines confirming its traditional use in psoriasis treatment and also emphasizes the need for antipsoriatic evaluation in animal models.